A Randomized Phase 4 Study of Immunogenicity and Safety After Monovalent Oral Type 2 Sabin Poliovirus Vaccine Challenge in Children Vaccinated with Inactivated Poliovirus Vaccine in Lithuania. (4th July 2020) - Bandyopadhyay, Ananda S; Gast, Chris; Brickley, Elizabeth B; Rüttimann, Ricardo; Clemens, Ralf; Oberste, M Steven; Weldon, William C; Ackerman, Margaret E; Connor, Ruth I; Wieland-Alter, Wendy F; Wright, Peter; Usonis, Vytautas
Abstract: Background: Understanding immunogenicity and safety of monovalent type 2 oral poliovirus vaccine (mOPV2) in inactivated poliovirus vaccine (IPV)–immunized children is of major importance in informing global policy to control circulating vaccine-derived poliovirus outbreaks. Methods: In this open-label, phase 4 study (NCT02582255) in 100 IPV-vaccinated Lithuanian 1–5-year-olds, we measured humoral and intestinal type 2 polio neutralizing antibodies before and 28 days after 1 or 2 mOPV2 doses given 28 days apart and measured stool viral shedding after each dose. Parents recorded solicited adverse events (AEs) for 7 days after each dose and unsolicited AEs for 6 weeks after vaccination. Results: After 1 mOPV2 challenge, the type 2 seroprotection rate increased from 98% to 100%. Approximately 28 days after mOPV2 challenge 34 of 68 children (50%; 95% confidence interval, 38%–62%) were shedding virus; 9 of 37 (24%; 12%–41%) were shedding 28 days after a second challenge. Before challenge, type 2 intestinal immunity was undetectable in IPV-primed children, but 28 of 87 (32%) had intestinal neutralizing titers ≥32 after 1 mOPV2 dose. No vaccine-related serious or severe AEs were reported. Conclusions: High viral excretion after mOPV2 among exclusively IPV-vaccinated children was substantially lower after a subsequent dose, indicating induction of intestinal immunity against type 2 poliovirus.